2020
DOI: 10.5005/jp-journals-10071-23528
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Efficacy of Pediatric Logistic Organ Dysfunction-2 Score in Pediatric Intensive Care Unit of Rural Hospital

Abstract: A bstract Aims and objectives Utility of pediatric logistic organ dysfunction-2 (PELOD-2) score on day 1 within 1 hour of admission in predicting mortality in children admitted in pediatric intensive care unit (PICU). Background Various scoring systems aid to evaluate the patient's mortality risk in the intensive care unit (ICU) by assigning a score and predicting the outcome. Critically ill children are characterized by large variations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
6
5
0
1
Order By: Relevance
“…The study by Karam et al ( 5 ) further showed the good calibration of the model, with a day 1 PELOD-2 AUC of 0.76 (95 CI 0.71–0.81) and Hosmer-Lemeshow test p = 0.76. Good Calibration and discrimination of PELOD-2 were also reported in the study by Deshmukh et al ( 34 ) (AUC = 0.93) and chi-square test for goodness of fit p = 0.45 in PICU patients with sepsis, further confirming the validity and reliability of the model.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The study by Karam et al ( 5 ) further showed the good calibration of the model, with a day 1 PELOD-2 AUC of 0.76 (95 CI 0.71–0.81) and Hosmer-Lemeshow test p = 0.76. Good Calibration and discrimination of PELOD-2 were also reported in the study by Deshmukh et al ( 34 ) (AUC = 0.93) and chi-square test for goodness of fit p = 0.45 in PICU patients with sepsis, further confirming the validity and reliability of the model.…”
Section: Discussionsupporting
confidence: 80%
“…A total of 29 studies were included for quantitative synthesis, among them, 18 studies that reported on the scoring systems PRISM-III/IV, ( 3 , 4 , 11 , 14 – 21 , 23 27 , 37 ), 11 studies that reported data on PIM-3 ( 3 , 4 , 7 , 14 , 16 , 18 , 20 , 28 – 31 ), and nine studies that reported data on PELOD-2 ( 5 , 14 , 16 , 28 , 32 36 ). Four studies were reported from India ( 4 , 7 , 17 , 34 ), two from Australia ( 20 , 32 ), two from China ( 20 , 32 ), two from Egypt ( 15 , 18 ), one from Pakistan ( 19 , 26 ), two from Korea ( 14 , 36 ), one from Mexico ( 21 ), one from Singapore ( 28 ), one from UAE ( 29 ), one from Indonesia ( 30 ), one from Africa ( 33 ), one from Saudi Arabia ( 11 ), two from Turkey ( 22 , 24 ), one from Sweden ( 23 ), one from Brazil ( 37 ), one from Switzerland ( 5 ), one from Thailand ( 27 ), one from Italy ( 31 ), and one multi-centric ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…The lower PELOD-2 score can partially explain the reduced mortality rate of the patients with MIS-C in our study. A study conducted in India found that a PELOD-2 score of 0–4 correlated with a 1.6% mortality rate, 5–9 correlated with a 14.8% mortality rate and 10–14 correlated with a 50% mortality rate [ 27 ]. In our study, of the two patients who passed away, Patient 1 had a PELOD- 2 score of 6 and Patient 9 had a PELOD-2 score of 9.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the nursing focuses can be determined, and the preventive measures can be taken in advance to minimize the pain and accidents of patients. It is a nursing method change from passive to active [20][21][22]. Compared with traditional nursing methods, predictive nursing is more systematic, comprehensive, and individualized and has more advantages [23].…”
Section: Computational and Mathematical Methods In Medicinementioning
confidence: 99%